Variation in the quality of charcoal from Acacia decurrens (J.C. Wendl.) Willd. with age and longitudinal stem portions - Minichil Mengistu; Yashwant S. Rawat; Anteneh T. Tekleyohannes; Sisay F. Asfaw (Trees, Forests and People)
Clean and safe energy use is vital for health, the quality of life and the socio-economic status of households. Charcoal is a primary source of fuel for urban and rural households in Ethiopia. Fast growing trees like Acacia decurrens (J.C. Wendl.) Willd., is nature's gift to the smallholder farmers for soil amelioration, the production of charcoal, fencing and wood for construction. The present study analyzed the physico-chemical and calorific value of Acacia decurrens charcoal of three age groups: 3, 5 and 7 years and three longitudinal stem portions: bottom, middle and top. The results showed a significant age-based variation in moisture content with magnitude ranging from 6.10% to 10.48%, in volatile matter from 20.05% to 26.33%, in ash content from 2.97% to 7.30%, in fixed carbon from 56.29% to 70.51%, in total carbon 82.61% to 90.56% and in basic wood density from 0.71 g‧cm-3 to 0.91 g‧cm-3. The mean calorific value of the charcoal of the three ages ranged from 24.89 MJ‧Kg-1 to 29.29 MJ‧Kg-1. The physico-chemical properties and calorific values of the charcoal were significantly different in age groups and longitudinal stem portions of Aacacia decurrens. Findings of this study are in line with the fact that with increasing basic wood density quality of charcoal increases.